Clinico-demographic Characteristics, Associated Anomalies and Treatment Profiles of Children presented with Undescended Testis at Medical University of Bangladesh - Alam, Shoheli; Islam, KM Didarul; Mahammad, Noor; Dilshad Munmun, Umme Habiba; Islam, Md Nowfel (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: The most common paediatric disorder among boy is undescended testis (UDT) which is usually identified during birth and these patients require proper treatment at the appropriate time due to increased risk of torsion, infertility, testicular cancer and associated inguinal hernia(>90%) as well as for cosmetic purposes. Objective: The purpose of this study was to determine side, palpability, age at presentation, associated anomalies and treatment plan in our institution. Methodology: This retrospective study was carried out in the department of Paediatric Surgery of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January 2017 to June 2019. Results: In this study 1.08% (213 children had UDT out of total paediatric outdoor 19803 patients) boys had UDT. They were aged from 7 months to 15 years (mean 5.61±3.81 years) at presentation. Only 16 (7.5%) patients presented within the 1 years of age in this study. 51.8% of patients presented at the age of >1yrs-5yrs. > 5yrs-10yrs of age was 33.5% cases and 13.6% of patients presented as late as 10yrs to 15 yrs. Unilateral UDT was found in 184 (86.4%) patients and bilateral was in 29(13.6%) patients. Right- sided unilateral UDT was in 112(52.6%) patients, left -sided unilateral UDT was in 72 (33.8%) patients. Palpable testis was found in 178(83.6%) patients and non-palpable found in 35(16.4%) patients. Associated anomalies of UDT were seen in 64(30%) patients. Hypospaedias was in 19(08%) patients and intersex disorders were in 15 (07%) patients. Orchidopexy was done in 192(90.1%) cases and orchidectomy was done only in 4(1.9%) cases. No testis was found in17 (08%) cases. Conclusion: UDT is one of the commonest disorders of paediatric age group. Very important issue is the early diagnosis and treatment of this anomaly. To treat the UDT in proper time help to optimize testicular function, earlier diagnosis of testicular malignancy, give cosmetic benefits and to prevent complications such as a clinical hernia or torsion. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 173-176